Особливості дисциплінарної відповідальності посадових та службових осіб Державної фіскальної служби України за порушення порядку здійснення адміністративних процедур - Луцик, А. М.; Lutsyk, A. M. (Право і безпека. - 2014. - № 4 (55). - С. 162-166, 2014)
Проаналізовано сучасні підходи до розуміння змісту поняття «дисциплінарний проступок». Сформульовано поняття дисциплінарного проступку посадових та службових осіб Державної фіскальної служби України за порушення порядку здійснення адміністративних процедур. Розглянуто підстави та види дисциплінарних стягнень, які можуть бути накладені на посадових та службових осіб Державної фіскальної служби України за порушення порядку здійснення адміністративних процедур. Виділено особливості дисциплінарної відповідальності посадових та службових осіб Державної фіскальної служби України за порушення порядку здійснення адміністративних процедур.

New approaches to understanding the content of the notion «petty offence» are analyzed. The concept of the petty offence by the officials and employees of the State Fiscal Service of Ukraine for violating the administrative procedures is formulated. The grounds and types of disciplinary penalties that can be imposed on the officials and employees of the State Fiscal Service of Ukraine for violating the administrative procedures are studied. The objective of the article is to analyze the current definitions that have been formed in the jurisprudence concerning the content of the concept of misconduct, to define the features of disciplinary responsibility of officials and employees of the State Fiscal Service of Ukraine for violating the administrative procedures. The methodological basis of the article is a set of general scientific and specific methods of research. With the help of logical and semantic method the author has defined the concept of «misconduct». Structural and logical method was used to determine the characteristics of disciplinary responsibility of officials and employees of the State Fiscal Service of Ukraine for violating the administrative procedures. It is emphasized that bringing officials and employees of the State Fiscal Service of Ukraine to disciplinary responsibility is possible only if there are certain conditions of legal and procedural nature. Peculiarities of disciplinary responsibility of officials and employees of the State Fiscal Service of Ukraine for violating the administrative procedures are distinguished.

Проанализированы современные подходы к пониманию содержания понятия «дисциплинарный проступок». Сформулировано понятие дисциплинарного проступка должностных и служебных лиц Государственной фискальной службы Украины за нарушение порядка осуществления административных процедур. Рассмотрены основания и виды дисциплинарных взысканий, которые могут быть наложены на должностных и служебных лиц Государственной фискальной службы Украины за нарушение порядка осуществления административных процедур. Выделены особенности дисциплинарной ответственности должностных и служебных лиц Государственной фискальной службы Украины за нарушение порядка осуществления административных процедур.
Features of disciplinary responsibility of officials and employees of the State Fiscal Service of Ukraine for violating the administrative procedures
Особенности дисциплинарной ответственности должностных и служебных лиц Государственной фискальной службы Украины за нарушение порядка осуществления административных процедур
Keywords: дисциплінарна відповідальність; Державна фіскальна служба України; посадові особи; державні службовці; дисциплінарні стягнення; адміністративні процедури; disciplinary responsibility; State Fiscal Service of Ukraine; officials; disciplinary penalties; administrative procedures; дисциплинарная ответственность; Государственная фискальная служба Украины; должностные лица; государственные служащие; дисциплинарные взыскания; административные процедуры